IMPROVING STUDENTS’ SPEAKING SKILL THROUGH ENGLISH MOVIE - Hariati, Puji (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
This study was aimed at finding out whether or not English movie can improve students’ speaking skills. This study was conducted by using Classroom Action Research. The population and the sample were the first grade students of AMIK Medicom in 2022/2023 academic year. This research applied quantitative and qualitative methods. The results showed improvements. The students' scores improved from cycle 1 to cycle 2.  In pre-test, the mean score was 33.52. In the first cycle, meeting 1 the mean score was 37.35, in meeting 2, 42.64 and meeting 3, 52.64. In the second cycle, meeting 1 the mean score was 64,41,  in meeting 2, 80 and meeting 3, 91.17. The improvements were seen in the percentage of the student’s achievement in speaking by using English movie; in pre-test, none of the students got 75 points. In the first cycle, in meeting 1, and meeting 2, there was also no student who got 75 points,  but in meeting 3 there was 23,52% (8 students) got 75 points. This means there was an improvement of about 23.52%. In the second cycle, in meeting 1 there was 29.41% (10 students) got 75 points, it means that there was an improvement of about 5.89%. In meeting 2 there was 79.41% (27 students) got 75 points, which means that there was an improvement of about 50%.  It means that English movie helped the students in speaking, listing supporting points, and making a simple outline to write events, places, or objects related to the topic.